Efficacy of a Combined Acceptance and Commitment Intervention to Improve Psychological Flexibility and Associated Symptoms in Cancer Patients: Study Protocol for a Randomized Controlled Trial - García-Torres, Francisco; Gómez-Solís, Ángel; Rubio García, Sebastián; Castillo-Mayén, Rosario; González Ruíz-Ruano, Verónica; Moreno, Eliana; Moriana, Juan Antonio; Luque-Salas, Bárbara; Jaén-Moreno, María José; Cuadrado-Hidalgo, Fátima; Gálvez-Lara, Mario; Jablonski, Marcin; et al. (Frontiers in Psychology, 2022)
Psychological flexibility is a key concept of acceptation and commitment therapy (ACT). This factor has been linked with psychological wellbeing and associated factors, such as quality of life, in cancer patients. These and other positive results of acceptation and commitment therapy in cancer patients found in previous research could be enhanced by using mhealth tools. A three-arm randomized superiority clinical trial, with a pre-post-follow-up repeated measures intergroup design with a 1:1:1 allocation ratio is proposed. A hundred and twenty cancer patients will be randomly assigned to one of the following interventions: (1) face-to-face ACT + mobile application (app), (2) face-to-face ACT, and (3) Waitlist control group. The primary expected outcome is to observe significant improvements in psychological flexibility acceptance and action questionnaire- II (AAQ-II) in the face-to-face ACT + app group, after comparing baseline and post-treatment scores, and the scores will remain stable in the two assessment points, 3 and 6 months after the intervention. Secondary expected outcomes are significant increasing scores in quality of life (EORTC QLQ C-30) and post-traumatic-growth (PTGI-SF), and significant decreasing scores in anxiety and depression (HADS), insomnia (ISI) and fatigue (BFI) at the same assessment points. Also, it is expected that the scores of this group will be higher than the scores of the face-to-face ACT group and the waitlist control group. This study aims to assess the efficacy of a combined intervention (face-to face ACT + app) for psychological flexibility and associated symptoms in cancer patients. The results of this protocol may help to consider the use of acceptation and commitment therapy and mhealth applications in cancer settings as a valid therapeutic choice. Clinical Trial Registration [www.ClinicalTrials.gov], identifier [NCT05126823].